(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Migraine is a prevalent and disabling neurological disorder characterized by severe, unilateral headaches often accompanied by nausea, light sensitivity, and sound sensitivity. Migraine is estimated to be the second most prevalent brain disorder after anxiety, affecting nearly 41 million adults. In Ayurveda it is correlated with Ardhavabhedaka, one of the Shiroroga out of 11 mentioned by Acharya Sushruta. Ardhavabhedaka is a Tridoshaja Vyadhi. The present case study is subjected to assess the efficacy of Marma Chikitsa and Ayurveda treatment in management of Ardhavbhedak. A 27 years old female patient came to our institute with complaint of experiencing on-and-off frontal headaches, predominantly left-sided, accompanied by nausea and sensitivity to light and sound. Marma Chikitsa, Pathyadi kwath 20ml BD with equal amount of water, and Shadbindu Tail Nasya was given for 21 days. Marma Chikitsa is used for pain management, while Pathyadi Kwath is specifically indicated for Shiroroga in Shrangdhara Samhita and Nasya Karma is considered as the best therapeutic intervention in Shiro Roga by Acharya Charaka. After 21 days of Marma Chikitsa significant improvements were noticed in pain management, while Shadbindu Tail Nasya and Pathyadi kwath also relieve other symptoms, resulting in overall improvement in the patient’s condition.